A Magic, Unquiet Body. (March 2016) - Edwards, Michael
The reading and rereading of modernist poetry in English can prompt the reflection that, in a fallen world awaiting the creation of "new heavens and a new earth, " poetry is a privileged showing of the "ecstasy" and "terror" (Eliot's terms) of our situation, and of its possibility. Under the action of poetry, the world, and language and poetry itself are each revealed as a kind of magic, unquiet body, a living body unlike any other, with a memory deeper than ours, ready for change. To this end, in the period of universal Anglospeak, the urgent task for the poet is to relearn the nature of English.